Phytochemistry, Pharmacology, and Toxicology of Datura Species-A Review - Meenakshi Sharma; Inderpreet Dhaliwal; Kusum Rana; Anil Kumar Delta; Prashant Kaushik (MDPI AG, 2021)
Datura, a genus of medicinal herb from the Solanaceae family, is credited with toxic as well as medicinal properties. The different plant parts of Datura sp., mainly D. stramonium L., commonly known as Datura or Jimson Weed, exhibit potent analgesic, antiviral, anti-diarrheal, and anti-inflammatory activities, owing to the wide range of bioactive constituents. With these pharmacological activities, D. stramonium is potentially used to treat numerous human diseases, including ulcers, inflammation, wounds, rheumatism, gout, bruises and swellings, sciatica, fever, toothache, asthma, and bronchitis. The primary phytochemicals investigation on plant extract of Datura showed alkaloids, carbohydrates, cardiac glycosides, tannins, flavonoids, amino acids, and phenolic compounds. It also contains toxic tropane alkaloids, including atropine, scopolamine, and hyoscamine. Although some studies on D. stramonium have reported potential pharmacological effects, information about the toxicity remains almost uncertain. Moreover, the frequent abuse of D. stramonium for recreational purposes has led to toxic syndromes. Therefore, it becomes necessary to be aware of the toxic aspects and the potential risks accompanying its use. The present review aims to summarize the phytochemical composition and pharmacological and toxicological aspects of the plant Datura.